2020
DOI: 10.3399/bjgpopen20x101077
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of the delivery of NHS Health Checks in general practice: an observational study

Abstract: BackgroundThe NHS Health Check programme aims to reduce the risk of common preventable diseases by providing risk information and behaviour change advice. Failure to deliver the consultation appropriately could undermine its efficacy. To date, to the authors’ knowledge, there are no published data on the fidelity of delivery of NHS Health Checks.AimTo assess the fidelity of delivery of NHS Health Checks in general practice.Design & settingFidelity assessment of video and audio recordings of NHS Health Chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Only one-third of older people screened for hazardous alcohol use during NHS Health Checks receive advice or feedback about their drinking. 44 Failing to raise concerns about alcohol intake following health screenings can provide a false sense of assurance to older people that their alcohol intake is safe. 15 Other barriers identified within this study, such as practitioners’ reservations about older people’s openness to alcohol-related discussion and making healthy lifestyle changes, may mean opportunities to motivate healthier decisions about alcohol use are not always taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one-third of older people screened for hazardous alcohol use during NHS Health Checks receive advice or feedback about their drinking. 44 Failing to raise concerns about alcohol intake following health screenings can provide a false sense of assurance to older people that their alcohol intake is safe. 15 Other barriers identified within this study, such as practitioners’ reservations about older people’s openness to alcohol-related discussion and making healthy lifestyle changes, may mean opportunities to motivate healthier decisions about alcohol use are not always taken.…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings highlighted opportunities to support older people's decisions about alcohol in UK primary care, wider evidence suggests practitioners may not capitalise on these to address alcohol. Only one third of older people screened for hazardous alcohol use during NHS Health Checks receive advice or feedback about their drinking (44). Failing to raise concerns about alcohol intake following health screenings can provide a false sense of assurance to older people that their alcohol intake is safe (15).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…A newly retrieved study reported that overall fidelity of delivery of NHS-HCs in general practice was high, however, important elements of the NHS-HC, including assessments in relation to ethnicity and family history of disease, in addition to the Alcohol Use Disorders Identification Test and dementia risk management, were being regularly omitted. 53 Another new study found that practitioners often demonstrated limited understanding and confidence in explaining the 10-year risk score to patients, whereas confidence in the JBS3 lifetime Open access CVD risk calculator, with its visual information summaries, was higher. 54 Objective 5: patient views on the NHS-HC programme Overall patient satisfaction levels with the programme were high, however the risk score was less helpful to patients than discussion about their health with the clinician during the NHS-HC.…”
Section: Principal Findingsmentioning
confidence: 99%
“…A study of 38 videorecorded NHSHCs found that QRISK2 was communicated in over 97% of cases, but did not report the extent of risk discussion or practitioner understanding. 22 …”
Section: Introductionmentioning
confidence: 99%
“…However, few captured views of those delivering the NHSHCs and none specifically considered CVD risk communication. A study of 38 video-recorded NHSHCs found that QRISK2 was communicated in over 97% of cases, but did not report the extent of risk discussion or practitioner understanding (22). This paper presents data from video-stimulated recall (VSR) interviews with NHSHC practitioners from the RIsk COmmunication in NHSHC (RICO) study (23).…”
mentioning
confidence: 99%